Antarktis - Killie, Barbro; Savinova, Tatiana; Kleivane, Lars; Lie, Elisabeth; Skaare, Janneche Utne; Nygård, Torgeir (Miljøgifter og radioktivitet i norsk fauna: inkludert Arktis og Antarktis, 1999)
Keywords: Antarktis; biologi; forurensning; zoologi

Report of the Norwegian Antarctic Research Expedition 1997/98 - Tveraa, Torkild (ed.); Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1999)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1997/98; biologi; geodesi; glasiologi; oseanografi

Miljøovervåking på Bouvetøya - Bakken, Vidar; Isaksen, Kjell; Mehlum, Fridtjof; Gjertz, Ian (Natur, 1997)
Keywords: Bouvetøya; biologi

Responses of terrestrial plants and invertebrates to environmental change at high latitudes - Callaghan, Terry V.; Sonesson, Mats; Sømme, Lauritz; Walton, D. W. H.; Christensen, T.; Block, W. C.; Drewry, D. J.; Laws, Richard Maitland; Pyle, John Adrian (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 1997)
Many invertebrates show flexibility in their life cycles and are likely to respond to changes in climate as they have in the past. However, changes in temperature and photoperiod may disturb the life cycles of some existing polar invertebrates while continuing to constrain the polewards migration of more temperate species. Higher plants are likely to have higher productivity as temperatures and atmospheric CO2 levels increase but this productivity will be reduced by exposure to increasing UV-B radiation. Higher plants migrate more slowly than the rate at which climate is predicted to change and many species will be trapped in supra-optimal climates. Both mosses and lichens can migrate faster than higher plants, propagules of non-polar species already reaching the Antarctic, but they have fewer mechanisms of responding to changing environments. Polar vegetation and ecosystems provide feedback to the climate system: positive feedbacks are associated with decreases in reflectivity and increased carbon emissions from warm ing soils. In the Antarctic, feedback and responses to environmental change will be smaller than in the Arctic because of the less responsive cryptogams which dominate the Antarctic, the paucity of Antarctic soils, and geographical barriers to plant and invertebrate migrations.
Publisher: Royal Society
Keywords: Antarktis; biologi; botanikk; klimaendringer; lav; moser; virvelløse dyr

Anatomy and microbiology of the digestive tract of the Adelie penguin - Olsen, Monica Alterskjær; Mathiesen, Svein Disch (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Antarktis; NARE 1996/97; biologi; pingviner; zoologi

Report of the Norwegian Antarctic Research Expedition 1996/97 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1996/97; biologi; geodesi; geologi; glasiologi; oseanografi

Cold tolerance in Tardigrada from Dronning Maud Land, Antarctica - Sømme, Lauritz; Meier, Terje (Polar Biology, 1995)
Survival at low temperatures was studied in three species of Tardigrada from Muhlig-Hofmannfjella, Dronning Maud Land, Antarctica. Both hydrated and dehydrated specimens of Echiniscus jenningsi, Macrobiotus furciger and Diphascon chilenense had high survival rates following exposure to -22 degrees C for ca. 600 days, and dehydrated specimens following 3040 days at this temperature. In hydrated E. jenningsi, mortality increased with the duration of exposure from 7 to 150 days at -80 degrees C, while mortalities of the two other species did not change. Hydrated specimens of all species were rapidly killed at -180 degrees C, but all species exhibited good survivorship in the dehydrated state after 14 days at -180 degrees C. In conclusion, hydrated tardigrades are able to survive extended periods at low temperatures, and dehydrated specimens are even better adapted to survive overwintering on Antarctic nunataks.
Keywords: Dronning Maud Land; biologi; biomonitorering; bjørnedyr; kuldetoleranse; virvelløse dyr

Antarktis: verdens siste villmark - Fothergill, Alastair (Cappelen, 1994)
Keywords: Antarktis; Sørishavet; biologi; natur

A bibliography of terrestrial biological research in Dronning Maud Land, Antarctica - Newton, I P; Cooper, J; Mehlum, Fridtjof; Thor, Göran (South African Journal of Antarctic Research, 1994)
A bibliography of terrestrial biological research in Dronning Maud Land, Antarctica, of 388 titles from 1954 to 1994 is provided as an aid to researchers working in the region.
Keywords: Dronning Maud Land; bibliografi; biologi

Nitrogen uptake in the Weddell Sea during late winter and spring - Kristiansen, Svein; Syvertsen, Erik E; Farbrot, Tove (Polar Biology, 1992)
Keywords: Sørishavet; Weddellhavet; alger; biologi

Fugle-og selundersøkelser på Bouvetøya i desember/januar 1989/90 - Bakken, Vidar (Norsk Polarinstitutt, 1991)
Publication Title: Meddelelser
Keywords: Bouvetøya; biologi; fugler; fugleregistreringer; ornitologi; pingviner; seler; zoologi

Virkninger av klimaendringer i polarområdene : bidrag til den interdepartementale klimautredningen - Kverndal, Arnt-Ivar; Elvebakk, Arve; Jaworowski, Zbygniew; Hansson, Rasmus (Norsk Polarinstitutt, 1990)
Publication Title: Norsk Polarinstitutt. Rapportserie
Keywords: Antarktis; biologi; drivhuseffekten; dyreliv; fiskeri; flora; havbruksnæring; havis; havnivå; isbreer; klimaendringer; klimagasser; permafrost; planter; polarområdene; vannressurser; økologi

Some Nitzschia and related diatom species from fast ice samples in the Arctic and Antarctic - Medlin, Linda K.; Hasle, Grethe Rytter (Polar Biology, 1990)
Some Nitzschia and closely related species have been examined in the light and electron microscopes from fast ice samples in the Arctic and Antarctic. Nitzschia neofrigida, forming arborescent colonies, and Nitzschia promare, forming loose ribbon colonies, are described as new species, both probably included in the distribution of other similar species. A new combination, Auricula compacta, represents the first report of this genus from ice samples. Colony formation is reported for the first time in Nitzschia arctica and Nitzschia taeniiformis. No biopolar species were found and several reports of Arctic species in Antarctic ice samples have been refuted.
Keywords: Antarktis; alger; biodiversitet; biologi; botanikk; diatomeer; fytoplankton; planteplankton; polarområdene